1999
DOI: 10.1128/mcb.19.3.2109
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles for Cyclin-Dependent Kinase Inhibitors p21 and p16 in the Mechanisms of Senescence and Differentiation in Human Fibroblasts

Abstract: The irreversible G 1 arrest in senescent human diploid fibroblasts is probably caused by inactivation of the G 1 cyclin-cyclin-dependent kinase (Cdk) complexes responsible for phosphorylation of the retinoblastoma protein (pRb). We show that the Cdk inhibitor p21 Sdi1,Cip1,Waf1, which accumulates progressively in aging cells, binds to and inactivates all cyclin E-Cdk2 complexes in senescent cells, whereas in young cells only p21-free Cdk2 complexes are active. Furthermore, the senescent-cell-cycle arrest occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

38
573
5
11

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 729 publications
(627 citation statements)
references
References 55 publications
(83 reference statements)
38
573
5
11
Order By: Relevance
“…In contrast, INK4 family members act only as suppressors for cell cycle progression Roberts, 1995, 1999;Reynisdottir and Massague, 1997). p16 INK4a is known as a speci®c suppressor for Cdk4 and its homolog Cdk6 (Byeon et al, 1998;Parry et al, 1999;Stein et al, 1999). Since we demonstrated that Survivin interacts with Cdk4 during the cell cycle, we investigated whether Survivin in¯uences the Cdk4/p16 INK4a complex.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, INK4 family members act only as suppressors for cell cycle progression Roberts, 1995, 1999;Reynisdottir and Massague, 1997). p16 INK4a is known as a speci®c suppressor for Cdk4 and its homolog Cdk6 (Byeon et al, 1998;Parry et al, 1999;Stein et al, 1999). Since we demonstrated that Survivin interacts with Cdk4 during the cell cycle, we investigated whether Survivin in¯uences the Cdk4/p16 INK4a complex.…”
Section: Discussionmentioning
confidence: 99%
“…54 The roles of both families in G 1 phase arrest and induction of differentiation and apoptosis have been thoroughly studied. [55][56][57][58] In SCC cells, the CIP1/KIP1 family appears to play a more important role than the INK4 family because p21 waf1/cip1 is strongly expressed but p16 INK4a is weakly expressed. 59,60 In the present study, p16 INK4a expression was not increased in the Mn-SOD antisense-transfected SCC cells, while p21 waf1/cip1 expression was increased and coordinated with the upregulation of Bax and downregulation of Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that such changes may be due at least in part to genetic destabilization that results from accidental re-entry into the cell cycle of cells that underwent prolonged p21 induction in the course of senescence. Transient p21 induction triggers growth arrest of senescent cells, whereas another CDK inhibitor, p16, appears to be responsible for maintaining this growth arrest after the decay of p21 (Alcorta et al, 1996;Stein et al, 1999). p16 (in striking contrast to p21) is frequently mutated in human tumors (Hall and Peters, 1996), including HT1080 ®brosarcoma used in the present study.…”
mentioning
confidence: 82%
“…p21 is also induced at the onset of terminal growth arrest during replicative senescence of aging ®broblasts (Noda et al, 1994). A transient surge of p21 expression in both replicative and accelerated senescence is followed by the induction of another CDK inhibitor, p16 INK4A , which remains at a high level and may be responsible for the maintenance of growth arrest in senescent cells after the decay of p21 (Alcorta et al, 1996;Robles and Adami, 1998;Stein et al, 1999).…”
mentioning
confidence: 99%